Sex differences and implications for translational neuroscience research workshop summary - Pankevich, Diana E., 1975-; Wizemann, Theresa M.; Altevogt, Bruce M. (National Academies Press, 2011)
"Biological differences between the sexes influence not only individual health but also public health, biomedical research, and health care. The Institute of Medicine held a workshop March 8-9, 2010, to discuss sex differences and their implications for translational neuroscience research, which bridges the gap between scientific discovery and application ..."--Summary.